Hollow α-Fe2O3 nanofibres for solar water oxidation: improving the photoelectrochemical performance by formation of α-Fe2O3/ITO-composite photoanodes. Issue 47 (17th November 2016) - Einert, M.; Ostermann, R.; Weller, T.; Zellmer, S.; Garnweitner, G.; Smarsly, B. M.; Marschall, R.
Abstract : Dense and hollow α-Fe2 O3 nanofibre photoanodes and core–shell-like α-Fe2 O3 /indium-tin oxide (ITO) nanocomposite photoanodes were directly prepared via electrospinning. Abstract : We demonstrate the synthesis and photoelectrochemical performance of high-aspect ratio dense and hollow α-Fe2 O3 nanofibres, and the formation of core–shell-like α-Fe2 O3 /indium-tin oxide (ITO) nanocomposites utilised as a photoanode for solar water splitting. α-Fe2 O3 nanofibres were prepared via a single-nozzle electrospinning technique using iron chloride (FeCl3 ) and poly(vinylpyrrolidone) (PVP) as precursors, followed by calcination. A new synthetic formation mechanism has been proposed taking into account the significance of three control parameters: (i) the iron precursor, (ii) the role of a co-solvent and (iii) the influence of the humidity on the tube evolution of α-Fe2 O3 nanotubes. Hollow α-Fe2 O3 fibres showed enhanced photocurrents and incident photon-to-current efficiency (IPCE) values compared to dense fibres, which are ascribed to the superior surface area of hollow fibres offering a good accessibility for the electrolyte and thus leading to improved mass transport. The photoelectrochemical properties of the α-Fe2 O3 nanofibres could be further enhanced by the combination with highly crystalline, uniform ITO nanocrystals ( Ø 10 nm), thus forming a core–shell-like α-Fe2 O3 /ITO fibre nanocomposite. The doubled photocurrent of the α-Fe2 O3 /ITO nanocomposite can most likely be attributed to the fast interfacial charge carrier exchange between the highly conductive ITO nanoparticles and α-Fe2 O3, thus inhibiting the recombination of the electron–hole pairs in the semiconductor by spatial separation.